PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DAN KUALITAS LAYANAN TERHADAP KEPUASAN ORANG TUA SISWA DI MIS RANTAU PANJANG - Muhammad Ibnu; Muhammad Fadhli (STKIP Pesisir Selatan, 2026)
Parental satisfaction is an important indicator in assessing the quality of educational services in Islamic schools (madrasas). This satisfaction is influenced by various factors, including the principal's transformational leadership and the quality of services provided to students and parents. This study aims to analyze the influence of the principal's transformational leadership and service quality on parent satisfaction at MIS Rantau Panjang, both partially and simultaneously. The study used a quantitative approach with a survey method. The study population was 169 parents, with a sample size of 119 respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis with the aid of Structural Equation Modeling (SEM). SEM-PLS was chosen because it can analyze the relationships between latent variables simultaneously and test both the measurement model (outer model) and the structural model (inner model) in a single analysis. Empirical findings regarding the magnitude of the influence of the principal's transformational leadership and service quality on parent satisfaction are expected to provide a basis for Islamic schools to improve the quality of leadership and educational services to achieve optimal parent satisfaction.